2015
DOI: 10.1042/bsr20150001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic aerobic swimming exercise promotes functional and morphological changes in rat ileum

Abstract: SynopsisSeveral studies have reported the gastrointestinal (GI) effects promoted by the physical exercise. Thus, we aimed to evaluate the influence of swimming exercise on the contractile reactivity, lipid peroxidation and morphology of rat ileum. Wistar rats were divided into sedentary (SED) and groups exercised for two (EX2), four (EX4), six (EX6) or eight (EX8) weeks, 5 days/week. Animals were killed; the ileum was removed and suspended in organ baths where the isotonic contractions were recorded. Lipid per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
2
7
1
Order By: Relevance
“…Numerous investigations aimed to examine the influence of aerobic exercise on oxidative stress markers were mostly focused on treadmill or cycle ergometer (Powers et al 2016). We've chosen to examine the effects of swimming training due to the fact that swimming is considered as a natural ability of rats and it has also been proposed as a convenient model for studying the physiological changes and stress response to training (Balci and Pepe 2012;Araujo et al 2015).…”
Section: Levels Of Reduced Glutathione (Gsh)mentioning
confidence: 99%
“…Numerous investigations aimed to examine the influence of aerobic exercise on oxidative stress markers were mostly focused on treadmill or cycle ergometer (Powers et al 2016). We've chosen to examine the effects of swimming training due to the fact that swimming is considered as a natural ability of rats and it has also been proposed as a convenient model for studying the physiological changes and stress response to training (Balci and Pepe 2012;Araujo et al 2015).…”
Section: Levels Of Reduced Glutathione (Gsh)mentioning
confidence: 99%
“…However, concerning the gastrointestinal tract, little is known about the effects of physical exercise. The exercise promotes ischemia and motor changes in the intestine and intestinal mucosa [35], and shows that swimming as an acute and chronic aerobic exercise reduces ileum reactivity to both KCl and CCh [15,16]; however the influence of anaerobic exercise of resistance was not evaluated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of acute and chronic swimming exercise have shown that acute exercise does not promote oxidative stress in rat ileum. Furthermore, there is an increase after four weeks of exercise, but after six to eight weeks, oxidative stress is reduced, showing that the body underwent physiological changes to adapt to exercise and returned to homeostasis [15,16]. However, regarding the strength exercise, there are not data showing its effect on the balance oxidative stress and antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effects of aerobic exercise on gastrointestinal tract, some studies have shown this influence on intestinal contractile responsiveness in a chronic approach (Rosa et al, 2005 ; de Lira et al, 2008 ; Araujo et al, 2015 ). On the other hand, studies focus on the acute effects of exercise on absorption of nutrients, intestinal mucosa, and gastrointestinal permeability (Pals et al, 1997 ; Lambert et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%